Contemporary military strategy and the Global War on Terror : US and UK Armed Forces in Afghanistan and Iraq 2001-2012 /: US and UK Armed Forces in Afghanistan and Iraq 2001-2012. (2014 copyright 2014) - Unknown
No abstract available